Teachers’ Beliefs on Students’ Home Language as a Resource in EFL Classroom (Studies in ELT and Applied Linguistics, 2021)
This is the age of multilingual turn. It advocates the inclusion of indigenous languages that the children bring to school from home as resource. At present, use of students’ home language as a resource in teaching and learning of a new language has become a vexing issue. The teachers’ beliefs on any issue determine the types of teaching learning activities that they use in the classroom. In this context, this paper aims at exploring the Nepalese English language teachers’ beliefs regarding the use of students’ home language in English as a foreign language (EFL) classroom, and why or how they form their respective beliefs. For this, I collected data from five ‘Grade ten’ English language teachers of different community schools in Kathmandu, taking in-depth interview with them. The data were analyzed qualitatively creating themes. The analysis shows that the English language teachers regard home language as a resource in EFL classroom, and they do so on the basis of their own theoretical understanding and practical experience in teaching.